INSTRUCTING TIPS FOF TEACHING READING SKILL FOR EFL LEANERS - Murotova, Gulnoz (Журнал иностранных языков и лингвистики, 2023)
The article examines the feasibility of using an authentic literary text in teaching reading in foreign language classes from the point of view of domestic and foreign methodologists. It also analyzes the main advantages of using a literary text in teaching reading and describes various approaches to organizing this process. Furthermore, article is dedicated to the problems that English language learners are faced in the process of doing a reading task. The author discusses psychological training of English learners, which help them to overcome a feeling of fear to read in English.